Efektivitas Penggunaan Dana Desa dalam Pemberian PMT Stunting di Desa Geneng - Ririen Kartika; Retno Febriyastuti Widyawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Stunting is a condition in which a child's physical growth is stunted or fails to grow, which is often measured by height rather than age. In Geneng village, stunting not only affects children's health but also affects their education and productivity in the future. Children who experience stunting are at higher risk of learning difficulties and contribute to the cycle of poverty. Providing additional food can be interpreted as providing additional food that has been considered for its nutritional value, but not to replace the main daily food. Further food for stunted toddlers is provided to monitor the growth and development process of children who experience stunting. Each village will budget the funds to help accelerate stunting reduction in their respective areas. This type of research is verification research. The research data obtained is used to prove the existence of doubts about information or problems in academic science. The study results showed that using village funds effectively handled stunting in Genang Village. The provision of PMT stunting for stunted toddlers in Geneng Village experienced a significant increase in weight and height. The results showed that 9 out of 13 stunted toddlers showed an increase in weight and height due to the provision of PMT. This study concludes that using village funds to provide PMT stunting is very effective.